Suplementy diety a prawa konsumentów - Dąbrowska, Anna; Janoś-Kresło, Mirosława (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
There are more and more food products on the market that are dietary supplements. It is a huge, growing and lucrative market. The primary purpose of diet supplements is to supplement a normal diet, possible shortages in diet, but this should be done under the supervision of a physician. Unfortunately, Poles rarely consult a doctor, preferring self-treatment. As it results from the inspections carried out, not all products are safe, have the correct composition and quality. In the article, considerations about dietary supplements were related to consumer rights. One of them is consumer education, which is the basis for making rational decisions and not being exposed to the undesirable effects of using, often excessively, dietary supplements. Subject literature and desk research were used for this purposeThere are more and more food products on the market that are dietary supplements. It is a huge, growing and lucrative market. The primary purpose of diet supplements is to supplement a normal diet, possible shortages in diet, but this should be done under the supervision of a physician. Unfortunately, Poles rarely consult a doctor, preferring self-treatment. As it results from the inspections carried out, not all products are safe, have the correct composition and quality. In the article, considerations about dietary supplements were related to consumer rights. One of them is consumer education, which is the basis for making rational decisions and not being exposed to the undesirable effects of using, often excessively, dietary supplements. Subject literature and desk research were used for this purpose
Keywords: suplement; dieta; prawa konsumentów; suplementy diety